A remote lab to support e-leaning on Programmable System-on-Chip (PSoC) - Felgueiras, Manuel Carlos (2019)
The design flow in analog and digital electronics are quite opposite as result of each area maturation state. So, are also the teaching methodologies, being challenging for both teachers and students. The electronic design in the digital field is centered in the use of microprocessor and FPGA based circuits using high level programing/configuring languages. In a different way, the analog design is traditionally based on the use of elementary components associated with macroblocks, such operational amplifiers in order to built-up the wanted mission circuit. Some analog programmable components, as the PSoC, are analogically configurable in a manner similar to those already used in the digital domain. The use of this type of components is not straightforward, being necessary to get some concepts traditionally not taught in the analog electronic classes. The training using PSoC is then indispensable to verify if the programmed circuit corresponds to the intended one.